Konsolidasi Data Warehouse untuk Aplikasi Business Intelligence - Rudy Rudy (ComTech: Computer, Mathematics and Engineering Applications, 2012)
As the business competition is getting strong, corporate leaders need complete data that as a basis for determining future business strategies. Similarly with management of company "A", a pharmaceutical company which has three distribution companies. Each distribution company already has a data warehouse to generate reports for each of them. For business operational and corporate strategies, chairman PT "A" requires an integrated report, so analysis of data owned by the three distribution companies can be done in a full report to answer the problems faced by the managemet. Thus, data warehouse consilidation can be used as a solution for company "A". Methodology starts with analysis of information needs to be displayed on the application of business intelligence, data warehouse consolidation, ETL (extract, transform and load), data warehousing, OLAP and Dashboard. Using data warehouse consolidation, information access by management of company "A" can be done in a single presentation, which can display data comparison between the three distribution companies.